THE PRINCIPLES BEHIND SOCIALIST FEMINISM MOVEMENT THROUGH THE FEMALE CHARACTERS IN CHERRY ORCHARD DRAMA - Ayu W., Maria Komang; Surya, Satyawati; Asanti, Chris (Fakultas Ilmu Budaya Universitas Mulawarman, 2022)
This research analyzes the principle behind the socialist feminism movement through the female characters in Cherry Orchard drama. Socialist feminism becomes the struggle to get equal in social and economic. This research classifies the female characters into four principles behind the socialist feminism movement, that uses the socialist feminism theory by Mandell. This research uses the qualitative-descriptive method to analyze the principles behind socialist feminism through the four female characters' experiences in Cherry Orchard drama. There are four principles behind the socialist feminism movement those are women’s position, women’s rights, women’s role, and women’s participation.